An investigation into the use of the method of spherical currents for the determination of scattered wave fields - Du Plessis, N M (Department of Mathematics and Applied Mathematics, 2016)
In this thesis an approximation method, the method of spherical currents, is advanced for the determination of scattered fields (acoustic and electromagnetic) from convex bodies for plane harmonic incident waves. The method is worked out for the scalar (acoustic) case and applied to sound soft and sound hard obstacles of a given shape. The surface fields and backscattering cross sections of these obstacles are calculated according to the method and the results are compared with those of other methods. For the vector (electromagnetic) case only the basic theory is worked out for a perfectly conducting convex body.